2005
DOI: 10.1038/sj.bjc.6602841
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of two randomised trials of early chemotherapy in asymptomatic metastatic colorectal cancer

Abstract: This report constitutes a prospectively planned meta-analysis combining two almost identical trials undertaken in Australasia and Canada to study the effect of starting chemotherapy immediately in asymptomatic patients with metastatic colorectal cancer. Patients (n ¼ 168) were randomised to receive either immediate or delayed treatment (at onset of predefined symptoms). Australasian patients received either weekly 5-fluorouracil and leucovorin (500 and 20 mg m À2 , respectively) (n ¼ 59) or the daily  5 Mayo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 20 publications
0
35
0
1
Order By: Relevance
“…23 However, a meta-analysis of 168 patients from two randomized trials of early chemotherapy in asymptomatic metastatic CRC concluded that early treatment did not provide a survival benefit, or improve QOL, compared with delaying treatment until symptoms occurred. 24 However, some experimental studies have suggested that the curability rate of chemotherapy decreases in proportion to the tumor volume. For example, the response of lung metastases of the Lewis lung tumor to single-dose cyclophosphamide has been studied as a function of the size of the metastases.…”
Section: Timing Of Chemotherapymentioning
confidence: 99%
“…23 However, a meta-analysis of 168 patients from two randomized trials of early chemotherapy in asymptomatic metastatic CRC concluded that early treatment did not provide a survival benefit, or improve QOL, compared with delaying treatment until symptoms occurred. 24 However, some experimental studies have suggested that the curability rate of chemotherapy decreases in proportion to the tumor volume. For example, the response of lung metastases of the Lewis lung tumor to single-dose cyclophosphamide has been studied as a function of the size of the metastases.…”
Section: Timing Of Chemotherapymentioning
confidence: 99%
“…Therapy metastatic colorectal cancer were analyzed by Ackland et al [35] There was no difference in overall quality of life or its individual domains between the two treatment strategies (immediate or delayed treatment at onset of predefined symptoms) at baseline, or at any subsequent time point. Early treatment of asymptomatic patients with metastatic colorectal cancer did life compared to withholding treatment until symptoms occurred.…”
Section: Screeningmentioning
confidence: 99%
“…Whereas the original Nordic study concluded that early treatment in asymptomatic patients with advanced CRC prolonged survival, asymptomatic period and time to progression (1992), a meta-analysis of two subsequent studies conducted in Canada and Australasia did not show significant improvement in survival and QoL to commence early treatment in asymptomatic patients (Ackland et al, 2005). Notably, the latter two studies terminated prematurely due to poor accrual.…”
Section: How Do We Treat the Elderly Poor Performance Status Or Asymmentioning
confidence: 99%